Pengolahan Sampah dan Limbah Rumah Pemotongan Hewan di Badan Usaha Milik Keluarga Segoroyoso - Erviana, Vera Yuli; Sukesi, Tri Wahyuni; Sulistyawati, Sulistyawati (CV. Rayyan Dwi Bharata, 2025)
Waste management is a pressing environmental issue, especially in developing countries like Indonesia. The increasing waste volume from slaughterhouses, including organic waste (blood, rumen contents, manure) and inorganic waste (plastic, metal), poses serious environmental threats if not properly managed. This study aims to improve community knowledge and skills in four key waste management aspects: (1) waste segregation for efficient processing, (2) maggot cultivation as an innovative organic waste solution, (3) rumen waste processing into biogas and organic fertilizer, and (4) sustainable waste residue management. Using a qualitative descriptive approach, data were collected through observation, interviews, and questionnaires. Results show that proper waste management minimizes pollution and enhances economic value through circular economy principles. Additionally, maggot cultivation reduces organic waste while generating income, and biogas production lowers energy costs. Government support and community participation are essential for sustainability. Effective slaughterhouse waste management benefits the environment while creating economic opportunities, ensuring long-term sustainability, better resource efficiency, and improved public health.